Active magnetic bearing for ultra precision flexible electronics production system - Tantau, Mathias (Cranfield University, 2015)
Roll-to-roll printing on continuous plastic films could enable the production of flexible electronics at high speed and low cost, but the granularity of feature sizes is limited by the system accuracy. Technologies such as gravure printing and nanoimprint lithography demand a level of rotary motion precision that cannot be achieved with rolling element bearings. Manufacturing tolerances of the rotating parts, thermal drift and process forces in combination with structural compliance add up to additional error motions. In this master by research an active magnetic bearing (AMB) solution is designed for a new, super-sized roll-to-roll flexible electronics production machine, which was so far based on hydrostatic bearings. The magnetic bearing could actively compensate the accumulated synchronous error and maintain high accuracy under all conditions. However, the asynchronous error of a conventional AMB with the required size and power is a problem. In order to reduce the relatively high positioning uncertainty of active magnetic bearings an innovative radial position measurement based on linear, incremental encoders with optical conversion principle is proposed. A commercial encoder scanning head faces a round scale with concentric, coplanar lines on its face. By counting these lines the radial position can be measured. Because such a scale is not readily available, it is made by micro-machining. In experiments, different machining methods are compared. Then a magnetic bearing is built to demonstrate the efficacy of the proposed sensor. As a result, the best measurement noise is 3.5nm at 10kHz and a position uncertainty of approximately 0.25µm has been achieved for the magnetic bearing. These promising results are especially interesting for applications with high precision requirements at low speed of rotation.
Keywords: Active magnetic bearing; AMB; Optical encoder; Flexible electronics; Plastic electronics; Roll-to-roll printing; R2R; Printing machine; Precision sensor; Magnetic bearing design; Grating; Micro-machining; Speedgoat; Imaging scanning principle